PREPARATION OF POROUS TITANIA AEROGEL BY CO2 SUPERCRITICAL EXTRACTION TECHNIQUE. - Silvester Tursiloadi (Jurnal Sains Materi Indonesia, 2004)
PREPARATION OF POROUS TITANIA AEROGEL BY CO2 SUPERCRITICAL EXTRACTION TECHNIQUE. Porous anatase titania that is attractive to its notable functions for photo catalysis and photon-electron transfer. A method for producing the porous anatase titania at low temperature is with dissolving of a titanium alkoxide in a methanol to give a titanium alkoxide solution, adding a mixed solution containing water, nitric acid catalyst and a methanol to the titanium alkoxide solution to perform hydrolysis and simultaneous polymerization to give a polymer solution (gel). The solvent in wet gels was super-critically extracted in CO2 at 60°C and 22 Mpa. Thermal evolution ofthe microstructure ofthe gels were evaluated by TGA—DTA, N2 adsorption, TEM and XRD. A porous titania, which has an anatase-form crystalline structure, an anatase-form particle diameter about 4 nm, average pore diameter of 13 nm, a BET specific surface area of 195 m2/g and a total pore volume of 0.55 cm2/g was obtained as prepared condition. The transformation of anatase phase to rutile phase occurred at 600 °C.